Do you Love Me? Attrition During Probation Period : Employee vs Employer - Sharma, Amalesh; Sharma, Kalpita Rani; Borah, Sourav Bikash (Prabandhan: Indian Journal of Management, 2011)
Indian economy is a resource based economy. The success of the corporate based economy generally depends on the human resource of the country. With huge infrastructural and educational development in India in the last decade, the human resources have emerged into a new era of excellent growth. But still, it seems that the supply of resources to the corporates is suffering. In this paper, the authors have attempted at finding find why there is huge attrition during probation period in Indian corporates. Is it the organizational culture or the lack of motivation among the employees? We attempted at seeing the live causes of high attrition during probation period. A theoretical framework is developed to enhance the understanding of the attrition trends and its probable cause. Our research findings state that there are many more critical elements than are actually considered. This research may be valuable to the HR managers while developing recruitment strategies. Again, this may be directed towards the next phase of attrition research on a much wider platform. The study contributes to the existing literature by examining the factors affecting attrition during the probation period, a relatively less researched area in a growing economy like India.